2011
DOI: 10.1016/j.jmps.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A finite strain model of stress, diffusion, plastic flow, and electrochemical reactions in a lithium-ion half-cell

Abstract: a b s t r a c tWe formulate the continuum field equations and constitutive equations that govern deformation, stress, and electric current flow in a Li-ion half-cell. The model considers mass transport through the system, deformation and stress in the anode and cathode, electrostatic fields, as well as the electrochemical reactions at the electrode/electrolyte interfaces. It extends existing analyses by accounting for the effects of finite strains and plastic flow in the electrodes, and by exploring in detail … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
271
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(278 citation statements)
references
References 45 publications
5
271
0
Order By: Relevance
“…The concurrent processes of Li transport, phase transformation and elasto-plastic deformation in Si anodes have inspired numerous modeling works [19][20][21][22][23][24][25] . Several groups developed models to explain the anisometric volume expansion of c-Si nanowires upon lithiation 14,18,24 .…”
Section: Introductionmentioning
confidence: 99%
“…The concurrent processes of Li transport, phase transformation and elasto-plastic deformation in Si anodes have inspired numerous modeling works [19][20][21][22][23][24][25] . Several groups developed models to explain the anisometric volume expansion of c-Si nanowires upon lithiation 14,18,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, this mechanical damage can be mitigated by nanostructuring the silicon anodes, as has been successfully demonstrated in nanowires [6,7], thin films [8][9][10][11][12], nanoporous structures [13,14], and hollow nanoparticles [15,16]. Specifically, recent experiments and theories indicate that one can prevent fracture by taking advantage of lithiation-induced plasticity [11,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have examined plastic deformation in Li x Si [5,12,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Sethuraman et al measured stresses during cycling of Li x Si electrodes, finding plastic flow, which results in dissipation of energy comparable to that of polarization losses [18].…”
Section: Introductionmentioning
confidence: 99%
“…Sethuraman et al further suggested that device designs that minimized stress formation during cycling would have improved charge/discharge capacities. Building off of this work, Bower et al developed an extensive analytical model of a simple layered LIB based on the field equations for coupled stress, diffusion, electric fields, and electrochemical reactions [180]. The model was able to reproduce most features of the potential and stress cycles originally observed by Sethuraman et al quite successfully, confirming the energy dissipation resulting from stress-potential coupling.…”
Section: Strain Segregation and Reactivitymentioning
confidence: 75%